Attitude to caesarean section amongst antenatal clients in Ibadan, Nigeria (2011)
This was a cross-sectional study carried out on 372 clients receiving antenatal care at a rural, suburban and urban centres, in order to assess the acceptance of caesarean delivery amongst them and the factors influencing their attitude. Caesarean section was acceptable to 65.7%. Many respondents will refuse the surgery, because they do not think abdominal delivery is natural or necessary. However, if indicated by their health caregiver to be necessary to save life, 78.3% would comply. Others would leave for a religious healing home, another hospital, a traditional birth attendant or be delivered at home. The cultural reasons why some women decline include feeling that caesarean delivery is due to “spiritual attacks”, retribution for maternal infidelity and failure of a woman to fulfil her reproductive function. Respondents were more likely to accept the surgery if they had heard of it before or had a previous caesarean delivery. They were less likely to accept it if they were Christians or attended the rural health centre. Age, parity and educational level had no influence. Only 4% of the respondents would request a caesarean section for non-medical reasons. Health education needs to be carried out in the community, as well as during antenatal classes, to address the cultural beliefs. Means of involving religious bodies in enlightenment campaigns to improve women's attitude should be explored.